Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s12034-011-0362-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in microstructural parameters of NB4D2 silk fibres due to electron irradiation: X-ray line profile analysis

Abstract: The present study is concerned with changes of microcrystalline parameters in NB4D2 (Bombyx mori) silk fibres, due to electron irradiation. The irradiation process was performed in air at room temperature using 8 MeV electron beam at different dose rates: 0, 25, 50 and 75 kGy, respectively. X-ray recording of these irradiated samples and the line profile analysis were carried out. The crystal imperfection parameters such as crystallite size 〈N〉, lattice strain (g in %) and surface weighted crystallite size (D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This early work was reviewed in a 1936 article . Originally, ultracentrifugation and light scattering techniques were used to detect both cleavage and aggregation of the protein molecules; however, more recently, infrared spectroscopy, , ultraviolet–visible spectrophotometry, crystallography, and wide-angle X-ray scattering have been used. Raman and FT-IR analysis showed that KrF excimer laser is capable of inducing conformational changes in irradiated collagen film mainly as a result of the breaking of the hydrogen bond network and loss of water molecules which maintain the ordered structure .…”
mentioning
confidence: 99%
“…This early work was reviewed in a 1936 article . Originally, ultracentrifugation and light scattering techniques were used to detect both cleavage and aggregation of the protein molecules; however, more recently, infrared spectroscopy, , ultraviolet–visible spectrophotometry, crystallography, and wide-angle X-ray scattering have been used. Raman and FT-IR analysis showed that KrF excimer laser is capable of inducing conformational changes in irradiated collagen film mainly as a result of the breaking of the hydrogen bond network and loss of water molecules which maintain the ordered structure .…”
mentioning
confidence: 99%